Differences in the parameters of calcaneal bone mineral density between elite track and field athletes, elite handball players and sedentary male controls - Šolaja, A.; Šolaja, M. (Facta Universitatis: Series Physical Education and Sport, 2017)
The aim of this study was to determine the differences between the parameters of dominant calcaneal bone mineral density of elite track and field athletes, elite handball players and sedentary male controls, as well as the values of these differences. A total of 90 healthy men, aged 18 to 30 took part in this study, elite track and field athletes (n=30), elite handball players (n=30) and sedentary controls (n=30). Bone mineral density measurements of the dominant calcaneus were done by using an ultrasound densitometer "Sahara" (Hologic, Inc., MA, USA). The following parameters were measured: Speed of sound (SOS), Broadband ultrasound attenuation (BUA), the aStiffness index (SI) and Bone mineral density (BMD). MANOVA revealed a significant difference between the group of elite athletes and the control group in all measured parameters of bone mineral density (p=0.00). There was no significant difference in measured parameters between track and field athletes and handball players, yet bone mineral density arithmetic mean of elite track and field athletes was higher (0.732 g/cm²) than it was in elite handball players (0.690 g/cm²), as well as all the other measured parameters. The results of this study shows that there is no difference between the values of bone mineral density parameters in highly trained track and field and handball male athletes. In addition to this, practicing these two high-impact sports has a significant impact on the values of the calcaneal bone density parameters compared to sedentary male controls.